Innovative Internationalization in Education of Civil Engineers at STU in Bratislava, the Slovak Republic - Cantarero, Pavla (Innovations in Pedagogy and Technology, 2025)
This paper presents experiences in teaching Slovak and international civil engineering students from various countries. The English language courses focus on the technical terminology used across 20 departments at the Faculty of Civil Engineering, STU in Bratislava. The study also introduces innovative approaches to engineering education developed as part of research at the Faculty of Arts, Comenius University in Bratislava. The research investigates three main aspects: internationalization of teaching, educational innovation, and the evaluation of teaching improvement. Details of teaching practice are presented, and proposals for future research design are outlined. A special type of European standard, known as Eurocodes, is gradually replacing national standards. Eurocodes enable design of load-bearing structures using materials such as aluminum alloys, concrete, fiber-reinforced polymers, glass, steel, timber, and composites. Since their terminology differs from that traditionally used in the UK, the USA, and Australia, Eurocodes offer a unique opportunity for language and technical education. Their availability in many languages makes them an extremely effective tool for teaching international students. This paper describes innovative education based on Eurocodes. Student feedback, teacher performance assessments, and seminar evaluations are presented. Key objectives include: (i) supporting local students in adapting to and benefiting from international practices (“internationalization at home”); (ii) meeting the needs of international students and effectively supporting their learning; (iii) critically evaluating teaching and student learning; and (iv) using a variety of approaches to enhance learning and assessment. Peer learning, in which students learn from one another without direct instructor involvement, is an especially effective method.